Precursor flow rate manipulation for the controlled fabrication of twin-free GaAs nanowires on silicon substrates. - Kang, J; Gao, Q; Parkinson, P; Joyce, H; Tan, H; Kim, Y; Guo, Y; Xu, H; Zou, J; Jagadish, C (2012)
Vertically oriented GaAs nanowires (NWs) are grown on Si(111) substrates using metal-organic chemical vapor deposition. Controlled epitaxial growth along the <111> direction is demonstrated following the deposition of thin GaAs buffer layers and the elimination of structural defects, such as twin defects and stacking faults, is found for high growth rates. By systematically manipulating the AsH(3) (group-V) and TMGa (group-III) precursor flow rates, it is found that the TMGa flow rate has the most significant effect on the nanowire quality. After capping the minimal tapering and twin-free GaAs NWs with an AlGaAs shell, long exciton lifetimes (over 700 ps) are obtained for high TMGa flow rate samples. It is observed that the Ga adatom concentration significantly affects the growth of GaAs NWs, with a high concentration and rapid growth leading to desirable characteristics for optoelectronic nanowire device applications including improved morphology, crystal structure and optical performance.